Southeast Asian Capitalists - McVey, Ruth Thomas (Book collections on Project MUSE., 1992)
This collection of essays explores the origins and roles of Southeast Asian business groups, especially as they developed during the 1970s and 1980s. An important contribution to studies of ethnic Chinese entrepreneurship in Southeast Asia. Includes a comprehensive introduction by the editor.